2020
DOI: 10.36028/2308-8826-2020-8-1-19-24
|View full text |Cite
|
Sign up to set email alerts
|

Technology of Development of Tactical and Technical Skills of Tennis and Badminton Players With the Use of Augmented Reality Devices

Abstract: The purpose is to elaborate the technology for the development of tactical and technical skills of tennis and badminton players with the use of augmented reality devices. Methods. In our research, we used the following methods: analysis and generalization of scientific and methodological literature, video analysis, optical coding of the playing field. Results. The research resulted in the elaboration of the innovative technology for the development of tactical and technical skills of tennis and badminton playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Konovalov I proposes: In badminton, with the continuous improvement of performance, it will be affected by various factors, among which physical training and technical tactics are more closely related. 6 Based on the above analysis, it can be found that, in the study of badminton physical training, it still stops at the level of traditional strength training, although the importance of the specialization of physical training is emphasized, there is no practical implementation analysis of this training, failed to systematically analyze how detailed physical training methods affect the quality or function of badminton players, in this way, the research stops on the surface of physical training, and it fails to better analyze which part of the quality has a higher correlation with the competitive ability of badminton players, and this happens to be the content that coaches and athletes need to pay attention to during training.…”
Section: Introductionmentioning
confidence: 99%
“…Konovalov I proposes: In badminton, with the continuous improvement of performance, it will be affected by various factors, among which physical training and technical tactics are more closely related. 6 Based on the above analysis, it can be found that, in the study of badminton physical training, it still stops at the level of traditional strength training, although the importance of the specialization of physical training is emphasized, there is no practical implementation analysis of this training, failed to systematically analyze how detailed physical training methods affect the quality or function of badminton players, in this way, the research stops on the surface of physical training, and it fails to better analyze which part of the quality has a higher correlation with the competitive ability of badminton players, and this happens to be the content that coaches and athletes need to pay attention to during training.…”
Section: Introductionmentioning
confidence: 99%